FRANCHISING IN ORGANIZED RETAIL IN HARYANA: ISSUES AND OPPORTUNITIES (IITM Journal of Business Studies, 2025)
The robust economy of Haryana, along  with steadily increasing levels of consumer  demand, translates to significant new business  potential for retail franchises. This paper  investigates the potential and difficulties in  depth, thereby providing insights into the  changing environment of organized retail in  Haryana. Results highlight the main issues  faced by the organized sector, specifically  in the five districts of Haryana: Ambala,  Faridabad, Gurugram, Kurukshetra, and  Panchkula. Data have been collected from a  sample of 320 respondents of different age  groups for the investigation of the study. From  the results, it has been found that at 0.86,  brand reputation and training and support  are favorably connected. Famous brands  train and aid franchisees more, where a high  brand reputation aligns with comprehensive  training. Marketing assistance and brand  reputation are positively associated (0.89).  High correlations between territory  protection and high royalty fees (0.77)  suggest that territory protection is linked to  higher royalty fees. The R-squared of 0.69  suggests the model explains many franchising  fluctuations. This high F-value indicates that  the model is statistically significant, with  an F-statistic of 116.24. Research indicates  that brand reputation, training and support,  and territory protection improve franchising  model effectiveness. However, large royalty  payments and statistically significant disputes  hurt franchising. It highlights the necessity of  adopting a strategic and flexible approach in  order to succeed in an ever-changing industry.  According to the findings of the study, there  is great potential for franchising in Haryana’s  organized retail sector. This, however, is  contingent upon franchisors being able to  manage the difficulties and effectively engage  with local partners.
Keywords: Franchisors; Foreign Direct Investment (FDI); Information Technology (IT); Indian Enterprises; Organized Sector; Retailers